The Role of Defense Diplomacy to Support Covid-19 Pandemic Responses Indonesia in 2019-2022 - Haryati Haryati (CV. AFDIFAL MAJU BERKAH, 2023)
The COVID-19 pandemic has impacted the economy, society, and the military. Defense diplomacy supports efforts to tackle the COVID-19 pandemic in Indonesia in 2019–2022 by involving the TNI in logistics, public health regulations, and restrictions on movement and large gatherings. This research uses a qualitative method, which is based on the philosophy of postpositivism or interpretivism, to research natural object conditions. The researcher is the key instrument; data collection is done by triangulation (observation, interview, and documentation); data analysis is inductive or qualitative; and research results are more understanding. This research resulted in several findings: 1) Defense Diplomacy provided TNI combat equipment and health services during the COVID-19 pandemic response period in Indonesia in 2019–2022. The health diplomacy strategy emphasizes the creativity of health diplomacy as a bureaucratic institution to communicate more inclusively, effectively, and efficiently. 2) Health diplomacy is less well implemented in bilateral relations with other countries. 3) The obstacles faced have hampered health diplomacy, so to strengthen international relations, health diplomacy must be utilized properly. TNI and Ministry of Health personnel should improve health diplomacy by: 1) To increase the supply of vaccinations from abroad, health diplomacy should be enhanced with possible partners. 2) To legally import vaccinations from abroad, the TNI, the Ministry of Health, and the private sector should form a Joint Secretariat for Health Diplomacy.